Crystal structure of N-(tert-butyl)-2-(N-(2-fluorophenyl)-2-(4-nitrophenyl) acetamido)-3-oxo-3-phenylpropanamide, C27H26FN3O5 - Zhang Meng-Di (Zeitschrift für Kristallographie - New Crystal Structures, 2015)
C27H26FN3O5, triclinic, P1̄ (no. 2), a = 10.8141(6) Å, b = 11.0261(6) Å, c = 11.9967(7) Å, α = 83.398(4)°, β = 65.586(3)°, γ = 81.088(4)°, V = 1284.7 Å3, Z = 2, Rgt(F) = 0.0490, wRref(F2) = 0.1519, T = 296 K.